2015
DOI: 10.1371/journal.pone.0145944
|View full text |Cite
|
Sign up to set email alerts
|

HIF3A DNA Methylation Is Associated with Childhood Obesity and ALT

Abstract: Gene polymorphisms associated so far with body mass index (BMI) can explain only 1.18–1.45% of observed variation in BMI. Recent studies suggest that epigenetic modifications, especially DNA methylation, could contribute to explain part of the missing heritability, and two epigenetic genome-wide analysis studies (EWAS) have reported that Hypoxia Inducible Factor 3 Alpha Subunit (HIF3A) methylation was associated with BMI or BMI change. We therefore assessed whether the HIF3A methylation is associated with obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 37 publications
0
59
2
Order By: Relevance
“…was linked to higher BMI and this relationship was present in both subcutaneous adipose tissue (SAT) and whole blood which was successfully replicated by others [76][77][78][79]. Other studies identified significant correlations of multiple genes (either involved in insulin and glucose metabolism, adipogenesis or early development) with BMI or other clinical variables related to obesity and adipose tissue distribution (e.g.…”
Section: Genome Wide Dna Methylation Analysis In Obesity and Associatmentioning
confidence: 62%
“…was linked to higher BMI and this relationship was present in both subcutaneous adipose tissue (SAT) and whole blood which was successfully replicated by others [76][77][78][79]. Other studies identified significant correlations of multiple genes (either involved in insulin and glucose metabolism, adipogenesis or early development) with BMI or other clinical variables related to obesity and adipose tissue distribution (e.g.…”
Section: Genome Wide Dna Methylation Analysis In Obesity and Associatmentioning
confidence: 62%
“…Human lifestyle and nutritional status were also believed to affect DNA methylation levels (Niculescu, 2012). High fructose or fat intake could induce DNA methylation, suggesting DNA methylation is involved in the metabolism of human body (Ohashi et al, 2015;Wang et al, 2015). According to the liver is the human body's largest metabolism organ, there is increasing evidence that DNA methylation also participated in pathological process of various liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…HIF3A, SREBP1, CPT1A, ABCG1, TXNIP, PHOS-PHO1) in multiple cohorts and in different ethnicities. [23][24][25][26][27][28][29][30] A recent EWAS, the largest of its kind to date (n = 10,261), showed that body mass index (BMI) as a measure of obesity, is associated with widespread changes in DNA methylation in genes involved in metabolic and inflammatory pathways. 31 In most human studies the methylation changes are measured when the obese or diabetic phenotype is already present, and it is therefore difficult to establish whether the observed DNA methylation changes are on the causal pathway to develop the disease or whether they are a consequence of the phenotype.…”
Section: Epigenetics and Metabolic Health In Humansmentioning
confidence: 99%